Classical and Christian ideas in English Renaissance poetry : a student's guide - Rivers, Isabel (London ; New York : Routledge, 1994)
"Since its first publication Isabel Rivers' sourcebook has established itself as the essential student guide to English Renaissance Poetry. It provides an account of the main classical and Christian ideas, outlining their meaning, their origins and their transmission to the Renaissance; illustrates the ways in which Renaissance poetry drew on classical and Christian ideas; contains extracts from key classical and Christian texts and relates these to the extracts of the English poems which draw on them; and includes suggestions for further reading, and an invaluable bibliographical appendix. In this new edition, the bibliographies have been updated to take account of important recent publications in philosophy, religion and Renaissance studies."--BOOK JACKET.
The golden age and the garden of eden -- The pagan gods -- Platonism and neoplatonism -- Stoicism -- Views of history -- Cosmology -- Reformation and counter-reformation -- Protestant theology -- Humanism -- BIblical exegesis and typology -- Theories of poetry -- Allegory -- Numerology.
Includes bibliographical references and index.
Keywords: English poetry -- Early modern, 1500-1700 -- History and criticism; Christian poetry, English -- History and criticism; English poetry -- Classical influences; Christianity and literature; Renaissance -- England; Classicism -- England; English poetry -- Criticism